2012
DOI: 10.1037/a0024946
|View full text |Cite
|
Sign up to set email alerts
|

A test of the bidirectional association between sleep and mood in bipolar disorder and insomnia.

Abstract: The present study investigates sleep, mood, and the proposed bidirectional relationship between the two in psychiatric disorders. Participants with interepisode bipolar disorder (n = 49), insomnia (n = 34), and no psychiatric history (n = 52) completed seven consecutive days of sleep diaries and mood measures. The interepisode bipolar and insomnia participants exhibited greater sleep disturbance than the healthy control individuals. Negative mood was equally heightened in both interepisode bipolar disorder and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 83 publications
6
62
1
2
Order By: Relevance
“…Non-clinical controls exhibited significantly better sleep quality than other participants, corroborating existing evidence of poorer subjective sleep quality in individuals with BD (Harvey et al, 2005;Millar et al, 2004;Ritter et al, 2012;Talbot et al, 2012), BHR individuals (Ritter et al, 2012), and individuals with fibromyalgia (Osorio et al, 2006;Theadom and Cropley, 2008). We observed similar levels of sleep disturbance in individuals with BD compared to individuals at BHR, corroborating existing findings (Ritter et al, 2012).…”
Section: Summary Of the Findingssupporting
confidence: 93%
“…Non-clinical controls exhibited significantly better sleep quality than other participants, corroborating existing evidence of poorer subjective sleep quality in individuals with BD (Harvey et al, 2005;Millar et al, 2004;Ritter et al, 2012;Talbot et al, 2012), BHR individuals (Ritter et al, 2012), and individuals with fibromyalgia (Osorio et al, 2006;Theadom and Cropley, 2008). We observed similar levels of sleep disturbance in individuals with BD compared to individuals at BHR, corroborating existing findings (Ritter et al, 2012).…”
Section: Summary Of the Findingssupporting
confidence: 93%
“…Recent studies have shed light in the neurobiological association between sleep and bipolar disorder. The studies reveal that the sleep disturbances are present not only during mood episodes but also in the interepisode intervals leading to significant impairment of functioning (Giglio et al, 2009;Talbot et al, 2012). Various pathophysiological processes are involved in the dysregulation namely alterations in melatonin levels, variations of clock genes and chronotypes (Abreu and Bragança, 2015; Robillard et al, 2013).…”
Section: Influence Of Sleep Qualitymentioning
confidence: 97%
“…Accruing empirical evidence suggests that sleep disturbance is a key, yet under-recognized, aetiological contributor to a range of psychiatric disorders (Talbot et al, 2012). A meta-analysis of 21 studies on the relationship between sleep disturbance and depression showed that pre-existing insomnia doubled the risk for depression 1 year or more later (Baglioni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%